Signalling pathways implicated in early mammary gland morphogenesis and breast cancer. - Beatrice Howard; Alan Ashworth (PLoS Genetics)
Specification of mammary epithelial cell fate occurs during embryogenesis as cells aggregate to form the mammary anlage. Within the embryonic mammary bud, a population of epithelial cells exists that will subsequently proliferate to form a ductal tree filling the stromal compartment, and which can produce milk upon terminal differentiation after birth. Subsequently, these structures can be remodelled and returned to a basal state after weaning before regenerating in future pregnancies. The plasticity of the mammary epithelial cell, and its responsiveness to hormone receptors, facilitates this amazing biological feat, but aberrant signalling may also result in unintended consequences in the form of frequent malignancies. Reflecting this intimate connection, a considerable number of signalling pathways have been implicated in both mammary gland morphogenesis and carcinogenesis.